(untitled) (Impetus, 2021)
The fight is considered one of the major sports to historical level, it was in the Olympic Games of antiquity, also was one of the first sports that took power in Greece in 1896, in his first appearance in the modern Olympic Games, for your competition is divided by weight, ie categorical systems and in two specialties, wrestling and Greco-Roman wrestling, the division seeks competitive and physical balance, this is more envision conditional techniques of capabilities, tactical, psychological and athletes. During the past 20 years the International Federation of Associated Wrestling (FILA) has made a lot of modifications to the rules to increase the number of qualifying shares and reducing the time of competition, changes have generated a change of physical training, with this premise resistance became the object of study in this research, which has served to determine the level of athletes as this capacity is concerned and what the most viable to train the same method would, therefore the objective layout was to compare the effect of two plans endurance training, an intermittent method and another interval applied for 4 weeks at Antioquia fighters.